Configuration of the active region for the Ge-on-Si photodetector based on carrier mobility - Chang, Chang; Xie, Xiaoping; Li, Tiantian; Cui, Jishi (Frontiers in Physics, 2023)
The design of Ge-on-Si photodetectors inspired by the mobility difference between electrons and holes is conducted. The electron mobility is about 2.8 times that of the hole’s, the electron and holes’ transport time in PIN junction could be equalized by setting the width difference between n and p-type slab. For the vertical PIN junction photodiodes, n-type slab devices show 20 GHz wider opto-electronic bandwidth than p-type slab devices. For the lateral PIN junction, the bandwidth would increase ~3 GHz when the length of the n-type silicon slab extended to 2.8 times that of the p-type slab. The bandwidth would decrease with the extended p-type slab. The optimized unbalanced PIN junction could also reduce the light absorption induced by the electrodes, then improve the photodetectors’ responsivity with no additional fabrication complexity.